Folklore come egemonia. Comprendere la cultura popolare; riconoscere la subalternità; lottare sul terreno della cultura? - Deiana, Alessandro (International Gramsci Journal, 2023)
This article intends to expound the idea that folklore and, more generally, popular culture cannot be identified only with the material and symbolic life of subaltern groups and classes, but must also be considered as the product and the incorporation of élite and ruling class hegemony. Reconnecting folklore to hegemony is the consequent, logical and dialectical solution of the Gramscian idea of folklore as subalternity. This relationship, investigated in this article through the paradigmatic cases of folklorism and heritage, can help us to understand the dynamics of contemporary popular culture; to recognize old and new forms of subalternity; to make a contribution to the criticism of bourgeois and liberal hegemony, beyond any exclusively culturalist approach.